Regulating Greenhouse Gases from Ships: Some Light at the End of the Funnel? - Ringbom Henrik (Cambridge University Press, 2022)
Developing standards for reducing greenhouse gas (GHG) emissions from ships involves various challenges of a technical, regulatory and political nature. The main role of the 1982 UN Convention on the Law of the Sea (LOSC) here, as with the prevention of pollution from ships more generally, is to ensure that a uniform set of standards applies across the globe. What those standards should be is up to other institutions to decide: the LOSC does not specify which institution(s) should be in charge, or even whether there is an obligation for any institution to act in this field. However, pressure from multiple directions has been mounting on the international maritime community to achieve significant reductions in GHG emissions from shipping. The perspective taken in this chapter is mainly an institutional one, focusing on the inter-relatedness and interaction between different legal regimes in a matter which still struggles to find its regulatory format.
The Law of the Sea and Climate Change: Solutions and Constraints